The Enchanted Castle - Nesbit, E. (Edith), 1858-1924 (Salt Lake City, UT : Project Gutenberg, 2002)
"The Enchanted Castle" by E. Nesbit is a children's fantasy novel published in 1907. Three siblings exploring during school holidays discover a mysterious country estate with marble statues, a maze, and a sleeping princess. When they find a magic ring that grants wishes, enchantment becomes real$1 (Bbut magic proves unpredictable and dangerous when wishes aren't carefully worded. Written for both children and adults, the novel blends imaginative play with subtle supernatural elements. (This is an automatically generated summary.)s
There is an improved edition of this title, eBook #34219
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Enchanted_Castle
Release date is 2002-11-01
Keywords: Fantasy fiction, English; Friendship -- Juvenile fiction; Siblings -- Juvenile fiction; Magic -- Juvenile fiction; Wishes -- Juvenile fiction; Castles -- Juvenile fiction; Rings -- Juvenile fiction; Great Britain -- History -- Edward VII, 1901-1910 -- Juvenile fiction